Nontraumatic subdural hematoma in patients on hemodialysis with end-stage kidney disease: a systematic review and pooled analysis - Yang, Liling; Li, Zongping; Dai, Xiaoyu; Wang, Lijun; Wang, Xiaoyi; Liu, Hongyuan (Frontiers in Neurology, 2023)
The original treatment may aggravate when hemodialysis (HD) patients have nontraumatic subdural hematoma (NSDH). End-stage kidney disease patients are at increased risk for NSDH, but its risk factors and outcomes are not sufficiently explored at present.Methods: Electronic databases, including PubMed, EMBASE, and Web of Science were searched by using various combinations of the keywords "Hemodialysis," "Renal Insufficiency," "Extracorporeal Dialysis," "Subdural Hematoma," "Subdural Hemorrhage," "Subdural Hematomas," and "Subdural Hemorrhages" in accordance with the PRISMA guidelines. Sixteen papers were selected. Relevant patient data were extracted, aggregated, and analyzed.Results: A total of 74 patients were analyzed, including 37 male, 26 female, and 11 with no gender data, with a mean age of 56 years (range, 16-81 years). There were 43 patients with hypertension, 36 patients with diabetes, 16 patients who used oral anticoagulants before dialysis, and 10 patients with atrial fibrillation. The diagnosis of subdural hematoma (SDH) was made by computed tomography (CT) (n=51), carotid arteriography (n=7), surgical exploration (n=3), and autopsy (n=2). Forty cases underwent surgical treatment, including craniotomy and burr hole (or twist drill) drainage. The 1-year mortality rate of NSDH was 45.9%. The mortality rate after conservative treatment (61.8%) was higher than that after surgical intervention (32.5%). The mortality rate of NSDH in dialysis patients with atrial fibrillation and in those who used oral anticoagulants before hemodialysis (HD) was 90% and 81%, respectively.Conclusions: NSDH is rare in HD, and mortality is high if NSDH occurs in dialysis patients. Surgical intervention reduces the mortality from NSDH in patients on HD (p<0.02). Patients with atrial fibrillation and those who were taking oral anticoagulants before dialysis have a higher NSDH mortality (p<0.01).